Model Pendidikan Karakter Anak Usia Dini Dan Anak Usia Sekolah Dasar Di Jepang. - Budi Mulyadi (Diponegoro University, 2019)
The title of this paper is The character education of early childhood and elementery school age children in Japan. The main goal of this research is to know how to apply the character education of early childhood and elementery school age children in Japan. This research is the combination between liblary reaserach and field research. The step method used in this research is observation, interview, clasification, analysis, interpretasion and description. From the result of this paper in general can be describe there are uniqueness and differences from the application of character education of early childhood and elementery school age children in Japan. But there are similarities that both are very concerned with moral education and personality. Moral education and personality is not taught trough special subject but is applied in daily life.